Medical Narrative and the Rhetoric of Identification: The Many Faces of Anna White Dildane. Issue 11 (1st November 2016) - Crick, Nathan; Gabriel, Joseph M.
ABSTRACT: When Anna White Dildane, a prostitute and heroin addict, was committed to the Laboratory of Social Hygiene (LSH) in 1917, she was treated by a staff that anticipated the methods of the biopsychosocial model later developed by Engel. That is to say, the staff members believed that Anna's rehabilitation was contingent on a scientific diagnosis of the physical, mental, and social factors that underlay her condition. However, using Anna and the LSH as a case study, we draw from Latour to show the limitations of this "modern" method of diagnosis and treatment that persists today. Using Burke, we advocate for a pragmatic orientation focused on creating rhetorically oriented narratives whose aim is to help patients make judgments about their health and future, namely, by bringing about the experience of "form" capable of constituting new types of identification. Effective medical rhetoric thus adopts a method of persuasion that begins with the narrative and self-understanding of the patient, links aspects of that narrative with the technical expertise of physicians and other health care providers, and crafts a new, more specialized narrative attentive to the desires and constraints of a patient's form of identification that is ultimately the seat of judgment.